2004
DOI: 10.1016/j.jacc.2004.07.044
|View full text |Cite
|
Sign up to set email alerts
|

A hard look at angiotensin receptor blockers in heart failure

Abstract: Multiple trials over the past several years have examined indications for angiotensin receptor blockers (ARBs) in the treatment of left ventricular dysfunction, both acutely after myocardial infarction and in chronic heart failure. Yet despite these data, there is still confusion regarding the efficacy of ARBs as monotherapy in these patient populations, as well as the specific indications for combination ARB/angiotensin-converting enzyme (ACE) inhibitor therapy. We examine the key differences among the trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…It causes exercise intolerance, impairs quality of life, and has been associated with high morbidity and mortality. Although the existing pharmacological therapies, such as inhibitors of the renin-angiotensin-aldosterone system and β-adrenoreceptor blockers improved outcomes in CHF [1][2][3][4], they are still not optimal and cannot fully prevent progressive cardiac remodeling and dysfunction. Recently, several non-pharmacological therapies such as cardiac rehabilitation and ventilatory support have been developed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It causes exercise intolerance, impairs quality of life, and has been associated with high morbidity and mortality. Although the existing pharmacological therapies, such as inhibitors of the renin-angiotensin-aldosterone system and β-adrenoreceptor blockers improved outcomes in CHF [1][2][3][4], they are still not optimal and cannot fully prevent progressive cardiac remodeling and dysfunction. Recently, several non-pharmacological therapies such as cardiac rehabilitation and ventilatory support have been developed [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…110 Currently, there is no clear evidence that ARBs have a direct effect on SCD prevention, and they currently remain second line in patients with systolic heart failure after maximizing the treatment with ACE inhibitors or if the patient is intolerant to ACE inhibitors. 111 Effect of Aldosterone Antagonists on SCD Prevention in Post-MI Patients and in Patients With CHF. The Randomized Aldactone Evaluation Study (RALES) is a randomized, double-blind placebo controlled trial that compared spironolactone (n ¼ 822) versus placebo (n ¼ 841) in patients with severe heart failure.…”
Section: Effect Of Ace-i On Scd Prevention In Post-mi Patients and Inmentioning
confidence: 99%
“…This property accounts for the increased tolerability of ARBs (lack of kinin-mediated side effects), but it may also lower their efficacy, because kinins have been associated with beneficial effects such as peripheral vasodilation and inhibition of myocardial hypertrophy and fibrosis. 23, 24 The Candesartan in Heart Failure: Assessment of Reduction in Mortality and Morbidity (CHARM) Alternative Trial has shown that the administration of an ARB improves prognosis in those heart failure patients who are intolerant of an ACEI. 25 These data are consistent with previous studies in patients with chronic heart failure 26 or with post-infarction LV dysfunction or heart failure.…”
Section: Neurohormonal Antagonistsmentioning
confidence: 99%